THE EFFECT OF TOURISM IMAGE, SERVICE QUALITY, AND PROMOTION ON RELIGIOUS TOURISM INTEREST IN PRINGSEWU REGENCY - Fauzi, Fauzi; Suryanto, Tulus; Anggraeni, Erike; Nasor, Muhammad (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2020)
Interest in religious tourism in the Pringsewu Kapubaten, Indonesia is still relatively low. The purpose of this study is to reveal whether there is an influence of tourism image, service quality, and tourism promotion on the interest of Muslim religious tourism in the Pringsewu district. The research method used is a quantitative method using an accidental sampling technique. Data analysis techniques using multiple linear regression with the help of SPSS 19.0. The originality of the research lies in the sharia economic approach which is carried out to reveal descriptively the results of the influence of three independent variables on the interest of Muslim religious tourism in Pringsewu that have never been revealed by previous studies. The results of the study stated that the percentage contribution of the three variables together amounted to 51.9%. This explains that the image of Muslim religious tourism, service quality, and tourism promotion can be a strategy to increase the interest of Muslim religious tourism in the Pringsewu district.Keywords: Tourism Image, Service Quality, Religious Tourism, Tourism Interests, Tourism Promotion